BAG3 Protein Is Over‐Expressed in Endometrioid Endometrial Adenocarcinomas. Issue 2 (22nd July 2016) - Esposito, Veronica; Baldi, Carlo; Zeppa, Pio; Festa, Michelina; Guerriero, Luana; d'Avenia, Morena; Chetta, Massimiliano; Zullo, Fulvio; De Laurenzi, Vincenzo; Turco, Maria Caterina; Rosati, Alessandra; Guida, Maurizio
Abstract : Endometrioid endometrial cancer is the most common gynaecological tumor in developed countries, and its incidence is increasing. The definition of subtypes, based on clinical and endocrine features or on histopathological characteristics, correlate to some extent with patient's prognosis, but there is substantial heterogeneity within tumor types. The search for molecules and mechanisms implied in determining the progression and the response to therapy for this cancer is still ongoing. BAG3 protein, a member of BAG family of co‐chaperones, has a pro‐survival role in several tumor types. BAG3 anti‐apoptotic properties rely on its characteristic to bind several intracellular partners, thereby, modulating crucial events such as apoptosis, differentiation, cell motility, and autophagy. BAG3 expression in human endometrial cancer tissues was not investigated so far. Here, we show that BAG3 protein levels are elevated in tumoral and hyperplastic cells in respect to normal glands. Furthermore, BAG3 subcellular localization appears to be changed in tumoral compared to normal cells. Our results indicate a possible role for BAG3 protein in the maintenance of cell survival in endometrioid endometrial cancer and suggest that this field of studies is worthy of further investigations. J. Cell. Physiol. 232: 309–311, 2017. © 2016 Wiley Periodicals, Inc. Abstract : BAG3 protein levels has been analyzed for the first time in human endometrial cancer tissues. BAG3 anti‐apoptotic protein is over‐expressed in endometrial cancer cells. BAG3 could be a target of value for endometrioid endometrial cancer therapy.